The Mediating Role of Psychological Ownership and Job Satisfaction in Human Resource Management Practices and Employee Loyalty: A Case Study of Sichuan University of Technology - Juncai He; Teetut Tresirichod (Bright Publisher, 2024)
The objective of this research is to examine the influence of human resource management practices on employee loyalty, with a focus on the mediating effects of psychological ownership and job satisfaction. This investigation involves the collection of survey data from 600 educators at Sichuan University of Technology, located in the western region of China, to serve as a case study. The hypotheses posited within the theoretical framework were evaluated through the application of Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings of this research indicate that efficacious Human Resource Management practices not only directly augment employee loyalty but also substantially bolster employee loyalty through the enhancement of psychological ownership and the improvement of job satisfaction. This study corroborates the combined mediating role of psychological ownership and job satisfaction in the relationship between Human Resource Management practices and employee loyalty. This research offers novel perspectives for comprehending and addressing the issue of disparate resource allocation within Chinese higher education, considering the unique aspects of China's imbalanced educational resources. It furnishes critical insights for the enhanced management and motivation of faculty in higher educational institutions in the western regions, alongside pragmatic recommendations for educational policymakers and university administrators.